Anxiety and Individual Coping Strategies In Undergoing Isolation During the Covid-19 Pandemic - Ismiyati Yuliatun; Siti Rahmawati; Sri Lestari (Universitas 'Aisyiyah Yogyakarta, 2021)
Individuals exposed to the Covid-19 virus have consequences for isolation, both self-isolation and isolation in health services. During isolation, individuals may experience anxiety which needs to be managed with appropriate coping strategies. Purpose: to find out how the anxiety experienced by individuals in undergoing isolation and how the coping strategies that individuals have in dealing with the anxiety that arises when undergoing isolation during a pandemic. Methods: qualitative using a phenomenological study. Data collection was carried out by semi-structured interviews and observations on two mothers who underwent isolation. The data obtained were analyzed to find emerging themes. Results: There were 5 main themes related to anxiety and coping strategies used by individuals in undergoing isolation during the Covid-19 pandemic, namely conditions before and during isolation, factors that cause anxiety, symptoms of anxiety, coping and support strategies, effects of coping strategies and lessons learned from experience undergo isolation.